PENGARUH PROFITABILITAS, LIKUIDITAS, FIRM GROWTH, KEBIJAKAN DIVIDEN DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN MANUFAKTUR DI BEI - Dalvin Steven, Rosmita Rasyid (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study was to analyze the effect of profitability, liquidity, company growth, dividend policy and investment decisions on the value of the company in manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017. The method of selecting samples in this study was purposive sampling, while 33 companies were selected as samples. The technique of using data uses multiple regression analysis using the IBM SPSS Statistics 25. The results of this study show that profitability, dividend policy and investment decision are significantly positive related to firm value. Liquidity and firm growth are significantly negative firm value.